2014
DOI: 10.1155/2014/989348
|View full text |Cite
|
Sign up to set email alerts
|

The Radiation Problem from a Vertical Hertzian Dipole Antenna above Flat and Lossy Ground: Novel Formulation in the Spectral Domain with Closed-Form Analytical Solution in the High Frequency Regime

Abstract: We consider the problem of radiation from a vertical short (Hertzian) dipole above flat lossy ground, which represents the wellknown "Sommerfeld radiation problem" in the literature. The problem is formulated in a novel spectral domain approach, and by inverse three-dimensional Fourier transformation the expressions for the received electric and magnetic (EM) field in the physical space are derived as one-dimensional integrals over the radial component of wavevector, in cylindrical coordinates. This formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(61 citation statements)
references
References 9 publications
0
60
0
Order By: Relevance
“…In [2] it is shown that the electric field at the receiver's position above the ground level (x>0) can be expressed with the following integral formula (E LOS denotes the direct field), where:…”
Section: Integral Representations For the Received Electric Field Andmentioning
confidence: 99%
See 4 more Smart Citations
“…In [2] it is shown that the electric field at the receiver's position above the ground level (x>0) can be expressed with the following integral formula (E LOS denotes the direct field), where:…”
Section: Integral Representations For the Received Electric Field Andmentioning
confidence: 99%
“…The last part of this work is devoted to comparing the above mentioned SPMbased analytical expressions to a wellknown empirical model for path loss prediction, particularly Okumura -Hata [5]. This, as well as similar comparisons to be performed in the future, will eventually determine the extent to which the easily implemented model of [2] can be used for the purposes of radio wave coverage prediction in real life scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations